DISABILITY AND WORLD LANGUAGE LEARNING: INCLUSIVE TEACHING FOR DIVERSE LEARNERS - Dámaso Izquierdo-Alegría (Universitat Jaume I. Department of English Studies, 2019)
Reviewed by Dámaso Izquierdo Alegría GRADUN-ICS, Universidad de Navarra, Spain Universidad Internacional de La Rioja, Spain   This volume deals with a much-needed topic that, unfortunately, has not attracted enough attention in the domain of language learning research: the adoption of inclusive instructional practices to address diverse students' needs. The authors' backgrounds and professional experiences perfectly embody an essential aspect in this field: it must be undertaken from an interdisciplinary approach. Sally Scott is a senior researcher of the Association on Higher Education and Disability (AHEAD) with extensive experience with diverse students, including campus disability resource offices; Wade Edwards is a professor of French at Longwood University. They co-directed the Project LINC: Learning in Inclusive Classrooms, focused on the development and implementation of instructional techniques aimed at creating more inclusive foreign language learning environments in higher education. This project has already proved to be very fruitful (Scott and Edwards 2012, Edwards and Scott 2012, Scott, Hildebrandt and Edwards 2013), with influential results about a variety of domains, ranging from the attitudes of students with special needs towards foreign language learning, to the needs of temporary faculty members that may not be fully aware of the protocols and resources offered by their campuses to address the learning process of students with disabilities. One of its major outcomes is a website full of original and already published documents and resources that serve as an invaluable guide to build an inclusive environment in foreign language instruction. Much of their experience in this project and subsequent spin-off research is effectively integrated in this book. This book will be interesting and compelling not only for researchers specialized in the field of disability and foreign language learning, but also for many teachers that wish to adopt new inclusive strategies in their courses to foster equitable learning opportunities. Although the book focuses on university settings, many teachers from other instructional contexts will also find many useful ideas.